MODEL OF HUMAN RESOURCE PERFORMANCE IMPROVEMENT BASED ON HUMAN CAPITAL AND SOCIAL CAPITAL WITH THE MODERATION OF INFORMATION TECHNOLOGY - Budiarti Ningrum (UNISSULA, 2017)
This study investigates the effect of human capital and social capital on human resource performance, and the moderating effect of information technology. Based on a total sample of 88 respondents from the Technical Implementation Unit (UPT) of Monitor Radio Frequency Spectrum Class I Semarang and Yogyakarta which is analyzed using structural equation modeling based smartPLS 3.0, the results indicated that 1) human capital is positively related to social capital and human resorce performance; 2) social capital is positively related to human resorce performance; 3) information technology moderates the relationships between social capital and human resorce performance; and 4) information technology moderates the relationships between human capital and human resource performance.Keywords: Human capital, Social capital, Information technology, Human resource performance